Vasorelaxant Properties of Moringa oleiferaleaf extract: An in-vitro study on mice blood vessels - Sehrish Zaffar, Muniza Qayyum, Momina Khalid, Muhammad Robass Zia, Minahil Aftab, Waqar Ahmed Siddiqui (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Moringa oleifera is a plant rich in bioactive compounds, including flavonoids, polyphenols, and alkaloids, which have been shown to have numerous health benefits. In recent years, several studies have investigated the potential of Moringa oleifera in the treatment ofhypertension and diseases of vascular dysfunction. Aim: To observe the effect of M. oleifera leaf extract on contractility of aortic tissue of mice, in vitro. Methods: An animal-based in-vitro experimental study was carried out in Pharmacology Department of CMH Lahore Medical College and Institute of Dentistry from February 2022 to March 2023. Mice were euthanized with ketamine. Aortic tissue was dissected and mounted in the organ bath. For evaluation of vasodilatory effect, cumulative dose-response curve of M. oleifera leaf extract was obtained using increasing doses of the extract against1 µM adrenaline and 80 mM KCl, in group I and group II, respectively.Response was obtained through Powe rLab (AD Instruments, Australia). Results: A consistent decrease was recorded against adrenaline and KCl-induced contractions in aorta, resulting in vasodilation. IC50 was 0.068 mg and 0.161 mg, in group I and II, respectively. Difference between IC50 of both groups was statistically significant (p-value = 0.0008). Conclusion: Leaf extract of Moringa oleifera exerts smooth muscle relaxant effectin blood vessels, most likely through inhibition of calcium influx, mediated through Gq-signalling pathway as well as depolarization-dependent voltage operated calcium channels. Keywords: Moringa oleifera, dose-response relationship, trachea, aorta, calcium channels